1999
DOI: 10.1093/oxfordjournals.jbchem.a022556
|View full text |Cite
|
Sign up to set email alerts
|

Indispensability of Transmembrane Domains of Golgi UDP-Galactose Transporter as Revealed by Analysis of Genetic Defects in UDP-Galactose Transporter-Deficient Murine Had-1 Mutant Cell Lines and Construction of Deletion Mutants

Abstract: UDP-galactose transporter is a membrane protein localized in the Golgi apparatus. It translocates UDP-galactose from the cytosol into the Golgi lumen, thus providing galactosyltransferases with their substrate. We characterized murine UDP-galactose transporter through molecular cloning for the following purposes: (i) to elucidate the molecular bases underlying the genetic defects of murine Had-1 mutants, which are deficient in UDP-galactose transporting activity, and (ii) to obtain information that would help … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
30
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 26 publications
5
30
0
1
Order By: Relevance
“…As expected from previous truncation experiments (11), the cytoplasmic tails were interchangeable. However, exchanges of amino acid stretches that represent potential transmembrane domains inactivated the UGT with a single exception.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…As expected from previous truncation experiments (11), the cytoplasmic tails were interchangeable. However, exchanges of amino acid stretches that represent potential transmembrane domains inactivated the UGT with a single exception.…”
supporting
confidence: 86%
“…In contrast, the cytosolically located N-and C-terminal tails of murine UGT were found to be dispensable. Deletion of both ends affected neither the activity nor the subcellular destination of the UGT (11).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Complementation of mutants allowed the cloning of putative UDP-galactose transporter genes from human and Schizosaccharomyces pombe (6,10). Through PCR-based approaches and screening of libraries, murine, hamster, and Drosophila cDNAs were also isolated (6,7,11). Expression of these genes in Saccharomyces cerevisiae followed by in vitro transport assays into Golgi vesicles confirmed that the gene products actually transport UDP-galactose (12).…”
mentioning
confidence: 96%